Association between Current Smoking and Stent Thrombosis in Post-PCI Patients: A Clinical Observational Analysis - Khan, Farhat Ullah; Parvez, Muzdalfa; Khan, Naeem; Khan, Qasim Ullah; Khan, Imran; Khan, Muhammad Idrees (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the relationship between smoking and the incidence of stent thrombosis in post-PCI patients and determine the impact of smoking on stent thrombosis incidence and examine DAPT adherence among smokers and non-smokers. Methodology: A retrospective analysis was conducted from January 2023 to December 2023, involving 200 post-PCI patients (100 smokers and 100 non-smokers). Demographic data, stent thrombosis incidence, and DAPT adherence were collected. Stent thrombosis was categorized into early, sub-acute, late, and no thrombosis. A chi-square test was used to assess the association between smoking and stent thrombosis. Results: Of the smokers, 58% (58 patients) developed stent thrombosis, compared to 18% (18 patients) of non-smokers. A chi-square test revealed a significant association between smoking and stent thrombosis (p = 0.0004). Regarding DAPT adherence, 55% of smokers showed poor adherence, while only 20% of non-smokers were non-adherent. The findings emphasize the higher stent thrombosis risk among smokers, potentially due to both physiological effects and poor adherence to medication. Conclusion: Smoking significantly increases the risk of stent thrombosis in post-PCI patients. Smoking cessation and better adherence to DAPT are crucial for improving patient outcomes. Future studies should focus on smoking cessation programs and better adherence monitoring post-PCI.